The role of youth in the development of the creative industry = Rola młodzieży w rozwoju przemysłu kreatywnego - Budziewicz-Gruźlecka, Agnieszka (Zielona Góra: Faculty of Economics and Management Press)
Currently, the young generation develops in the vicinity of rapid technical and technological progress, which results in indispensable continuous access to the Internet. It is important to use this access skillfully, sensitizing young people to culture, which has a huge impact on the development of the creative industry. The aim of the article is to try to recognize how young people use cultural goods.
Keywords: przemysł kreatywny; zarządzanie rozwojem kreatywności; klasa kreatywna; edukacja młodzieży; rola młodzieży; creative industry; creative class; management of creative development